The Impact of Information Systems on the Performance of Human Resources Department: Utilizing HRIS for Administrative and Strategic Efficiency (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Owing to the revolution in information technology, the face of the contemporary workplace has changed and systems have been made more effective by introducing new techniques. Majority of the organizations have now understood the importance of information storage and retrieval. In this paper, we focus on how modern technology is helping in ensuring effectiveness of HR functions. Human Resource Information System (HRIS) is an opportunity for organizations to make the HR department administratively and strategically participative in operating the organization. The main objective is to understand the extent to which HRIS is being used in increasing the administrative and strategic functions of the HR department. For this purpose, we have conducted a survey of 18 HR Managers from various private corporations operating in Punjab. The results show that HRIS is positively used as a tool to achieve greater administrative efficiency by adding value in the department. However, all of its benefits are difficult of quantify. HRIS utility as a strategic tool is still not been fully recognized, and this is preventing the system to be used to its fullest potential. Suggestions and recommendations are provided.